Infrared Spectra of Fe2O3-Li2O-B2O3-MoO3 Glasses - S. Bhagat, L. (Asian Journal of Chemistry, 2010)
Changes in network structures of lithium-molybdenum-iron-borate glasses were investigated by means of infrared spectroscopy and X -ray analysis. Analysis of the network structures were carried out based on a (1) networks unmodified by MoO3 and (2) Fe2O3- modified network. The unmodified networks are made by three dimensional array of clusters with unmodified BO3 and BO4 groups. MoO3 reduction and FeZO3 addition both gives contribution to four coordinated boron which governs the glass structure.